PENGARUH MODEL PEMBELAJARAN WRITE AROUND TERHADAP KETERAMPILAN MENULIS NARASI SISWA KELAS III SDN BIRINGKALORO KABUPATEN GOWA - Rizki Mulyani; Aliem Bahri; Nur Khadijah Razak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Write Around learning model on the narrative writing skills of third-grade students at SDN Biringkaloro, Gowa Regency. The study employed a quantitative approach with a One Group Pretest–Posttest design, involving 22 students as the sample. Data were collected through tests and observations, and analyzed using descriptive statistics and a paired sample t-test. The results showed an increase in the average score from 67.00 to 86.00, and learning mastery improved from 45% to 100%. The implementation of the learning model reached 87% (high category), while student activity reached 83% (very high category). The hypothesis test showed a significance value of 0.000 (< 0.05), indicating that the Write Around model has a significant and positive effect on improving students’ narrative writing skills